Can feed additives be used to promote positive behaviour in laying hens? A review - Makinde, Taiwo O.; Adewole, Deborah I. (World's poultry science journal, 2022)
SUMMARYThe welfare of laying hens has been a subject of interest among consumers, breeders, and animal welfare organisations across the globe. Laying hens’ behaviour is an important indicator of their welfare and provides feedback on how they perceive their housing environment. A relationship is believed to exist between serotonin levels and other coordinating axes of the brain such as the hypothalamic-pituitary-adrenal axis, which regulates various types of behaviour, and this provides the opportunity to achieve specific targeted modulatory interventions. Despite increasing interest in the use of feed additives in poultry production, there are inconsistencies in their application to promote positive behaviour in laying hens because of several factors, including age, sex, housing system, and genotype of the hens. This mini review expounds on the use of various feed additives such as phytogenic substances, probiotics, essential oils, vitamins, minerals, amino acids, as well as dietary fibre additives for promoting positive behaviour and overall welfare of laying hens. Feed additives have previously been used extensively for their immunomodulatory, anti-inflammatory, antimicrobial, and anti-fungal properties in poultry production, but their potential for promoting positive behaviour in laying hens through physical, physiological, anxiolytic, anti-depressive, and neuromodulatory activities was reviewed in this article.